INTEGRATING ECOLOGICAL LITERACY IN INDONESIAN LANGUAGE LEARNING TO PROMOTE ENVIRONMENTAL BEHAVIOR - Dedi Setiawan; Rahmat Rahmat; Ismail ismail; Elihami Elihami (Universitas Majalengka, 2026)
The increasing complexity of environmental problems requires learning approaches that connect knowledge, literacy skills, and responsible environmental behavior. However, classroom practices often remain focused on cognitive achievement and have not sufficiently linked language learning with students’ real-life ecological actions. This study aimed to examine the integration of ecological literacy in Indonesian language and literature learning to improve students’ literacy skills and promote pro-environmental behavior. The study employed a quantitative approach with a pre-experimental one-group pretest-posttest design involving 30 fourth-grade students at a resource-limited primary school in Enrekang Regency, Indonesia. Data were collected through reading comprehension tests, essay writing tests, ecoliteracy questionnaires, classroom observations, document analysis, and teacher interviews. The intervention integrated ecological values into reading, writing, and literary activities through Project-Based Learning, Problem-Based Learning, and Experiential Learning. The results showed that students’ reading comprehension increased from 4.80 to 6.87, with a significant improvement based on the Wilcoxon signed-rank test (p < .001; r = 0.92). Students’ essay writing skills also improved from 11.23 to 15.73, with a significant difference based on the paired-sample t-test, t(29) = 18.15, p < .001, dz = 3.31. Classroom observations further indicated increased ecological awareness and participation in school-based environmental practices. These findings suggest that ecoliteracy-based Indonesian language and literature learning can create meaningful, contextual, and action-oriented learning experiences that support both literacy development and pro-environmental behavior.